2014
DOI: 10.1186/1746-4269-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of diversity and utilization of edible plants in arid and semi-arid areas in Benin

Abstract: BackgroundAgrobiodiversity is said to contribute to the sustainability of agricultural systems and food security. However, how this is achieved especially in smallholder farming systems in arid and semi-arid areas is rarely documented. In this study, we explored two contrasting regions in Benin to investigate how agroecological and socioeconomic contexts shape the diversity and utilization of edible plants in these regions.MethodsData were collected through focus group discussions in 12 villages with four in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
(91 reference statements)
4
23
0
Order By: Relevance
“…Moreover, children from minority ethnic groups had higher probability of meeting MDD in Houeyogbe than in Bopa owing to the purchase of foods close to their cultural food habits. This finding could confirm that the interplay of socio-cultural attributes and agroecological conditions could explain the diversity of food plants selected and used by communities (Segnon & Achigan-Dako, 2014).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, children from minority ethnic groups had higher probability of meeting MDD in Houeyogbe than in Bopa owing to the purchase of foods close to their cultural food habits. This finding could confirm that the interplay of socio-cultural attributes and agroecological conditions could explain the diversity of food plants selected and used by communities (Segnon & Achigan-Dako, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Strengthening the link between agriculture and dietary diversity can be proposed as one of the solutions to improve infant and young child nutrition. A study conducted in Benin by Segnon and Achigan-Dako (2014) showed that achieving food security can be fostered through production and consumption policies that include the valorization of wild edible plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of plant uses and management often arise from complementarity between socio-cultural (Segnon and Achigan-Dako 2014;van Andel et al 2015). We observed patterns of convergence in use and management between communities sharing a same cultural background and living in the same geographical area.…”
Section: Factors Influencing the Use Andmentioning
confidence: 82%
“…Spider plant is cultivated in some communities in East and West Africa (Abasse et al 2007;Oluoch et al 2009) as well as Asia (Arora 2014). The species is rather found wild or feral in other parts of Africa (Dovie et al 2007;Kidane et al 2015;Segnon and Achigan-Dako 2014). Initiatives for promoting the species in commercial farming systems are rapidly emerging, especially in East Africa (Onyango et al 2013) as a result of increased recognition of its multiple nutritional and health benefits (Omondi et al 2017).…”
Section: Introductionmentioning
confidence: 99%